2016
DOI: 10.3233/jad-160018
|View full text |Cite
|
Sign up to set email alerts
|

Memory Impairment at Initial Clinical Presentation in Posterior Cortical Atrophy

Abstract: Posterior cortical atrophy (PCA) is characterized by core visuospatial and visuoperceptual deficits, and predominant atrophy in the parieto-occipital cortex. The most common underlying pathology is Alzheimer's disease. Existing diagnostic criteria suggest that episodic memory is relatively preserved. The aim of this study was to examine memory performance at initial clinical presentation in PCA, compared to early-onset AD patients (EOAD). 15 PCA patients and 32 EOAD patients, and 34 healthy controls were enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Memory impairment may therefore be expected to yield poor results when used to distinguish PCA from EOAD. Our results are consistent with those of Charles and Hillis [ 9 ] and Ahmed et al [ 44 ], who found memory to be impaired in both PCA and typical AD patients. Kas et al [ 11 ], however, found that PCA patients performed better than typical AD patients on an episodic memory test, even during the early stages of PCA (≤ 3 years since onset).…”
Section: Discussionsupporting
confidence: 93%
“…Memory impairment may therefore be expected to yield poor results when used to distinguish PCA from EOAD. Our results are consistent with those of Charles and Hillis [ 9 ] and Ahmed et al [ 44 ], who found memory to be impaired in both PCA and typical AD patients. Kas et al [ 11 ], however, found that PCA patients performed better than typical AD patients on an episodic memory test, even during the early stages of PCA (≤ 3 years since onset).…”
Section: Discussionsupporting
confidence: 93%
“…Third, a further practical objective is to establish a common framework for cognitive screening, neuropsychological examination, and selection of cognitive outcome measures for trials involving individuals with PCA. There is a particular need for clarity regarding the evaluation of episodic memory in PCA [ 63 ]. As noted previously, memory tests with explicit visual demands in encoding and/or retrieval (e.g., Rey–Osterrieth figure copy) are unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…PCA is most commonly a visual variant of AD, but may result from dementia with Lewy bodies, Creutzfeldt-Jakob (Heidenheim variant), or other lesions or disorders involving the posterior visual cortex. PCA patients have better verbal fluency and somewhat less impaired episodic memory than typical AD, 86 and they differ from many dementias in having relatively preserved insight into their illness and a tendency to depression. Some investigators suggest that PCA is a focal Alzheimer neurodegeneration of the occipital, occipitoparietal, and occipitotemporal cortex 87,88 , and that there may be prior learning disabilities and a pre-existing vulnerability in the cortical visual systems 77 .…”
Section: Introductionmentioning
confidence: 99%